2021
DOI: 10.1186/s12909-021-02914-2
|View full text |Cite
|
Sign up to set email alerts
|

A feedback journey: employing a constructivist approach to the development of feedback literacy among health professional learners

Abstract: Background Feedback, if effectively provided by the teacher and utilised by the learner, enables improvement in academic performance. It is clear from current literature that the provision of feedback by teachers is not sufficient on its own to guarantee improvements as early university entrants may not be sufficiently equipped to effectively engage with feedback. Nonetheless, it is critical for health professional students to develop feedback literacy early, in order to prepare them for a prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Yet, despite the expectation mismatch and insigni cant change in feedback literacy score with the workshop, participants projected some positive changes regarding their feedback process as illustrated in Theme 4 of the ndings. This result is comparable to the three previously-mentioned studies on training on feedback literacy (11,12,13) where there were perceived usefulness and bene ts of structured feedback literacy training. Beyond projection, participants in this study actually demonstrated feedback-seeking behaviour; one participant actively asked the workshop facilitator for feedback on their workshop behaviours, and later on another participant asked how to give feedback to a lecturer on her teaching.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Yet, despite the expectation mismatch and insigni cant change in feedback literacy score with the workshop, participants projected some positive changes regarding their feedback process as illustrated in Theme 4 of the ndings. This result is comparable to the three previously-mentioned studies on training on feedback literacy (11,12,13) where there were perceived usefulness and bene ts of structured feedback literacy training. Beyond projection, participants in this study actually demonstrated feedback-seeking behaviour; one participant actively asked the workshop facilitator for feedback on their workshop behaviours, and later on another participant asked how to give feedback to a lecturer on her teaching.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, no reallife feedback practice was available. This pragmatic constraint concurs with O'Connor and McCurtin's ndings of where feedback literacy training should be located within the curriculum to bene t the learning outcomes of students (13).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Internationally, a number of health professional programs have attempted to address factors related to burnout, stress, and resilience in their curricula through the inclusion of educational workshops early in students' academic programs (Bird et al, 2020; Johnson et al, 2020; Kreitzer & Klatt, 2017; Wu & Oprescu, 2021). Some studies recommend a broader perspective, claiming that all aspects of teaching and learning need to be considered; for example, the manner in which educators provide feedback and communicate with students can help to improve self‐efficacy, and also peer support can be utilized within teaching and learning initiatives and induction material in order to facilitate coping strategies (Gibbons, 2010; O'Connor & McCurtin, 2021). While these educational supports and strategies have been reported as useful by students, it may also be worth considering the strategic timing of these supports, in order to maximize their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that feedback literacy contributes to learning, its measurement is needed as an objective way for educators to evaluate the students' capacities to participate in the feedback process [ 14 , 15 ]. Several tools have been developed to measure feedback literacy for health professions students [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%